CLINICAL AND LABORATORY CHARACTERISTICS OF PATIENTS WITH ISCHEMIC HEART DISEASE RESISTANT TO ACETYLSALICYLIC ACID IN PERIOPERATIVE PERIOD OF CORONARY ARTERY BYPASS GRAFT: RESULTS OF AN OPEN PROSPECTIVE STUDY - Yu. I. Grinshtein; A. A. Kosinova; I. Yu. Grinshtein; A. V. Kovalev; V. G. Sukhovol'skiy; A. A. Savchenko (Столичная издательская компания, 2016)
Aim. To study the clinical and laboratory characteristics of patients with stable angina that are sensitive or resistant to acetylsalicylic acid (ASA) before and after coronary artery bypass graft (CABG) surgery. Material and methods. Patients (n=60) with stable angina III-IV functional class, undergoing CABG, were included into the study. In the first postoperative day all patients started to take ASA in enteric form at a dose of 100 mg. To determine the sensitivity to ASA platelet aggregation induced by adenosine diphosphate (ADP 5μM) and arachidonic acid (1 mM) before and after incubation with ASA in vitro was studied one day before CABG and at the 1st and 10th days after CABG using an optical aggregometer. Dielectric properties of blood and its components were also studied with the original Fourier spectrometer. Results. The ASA-resistance rate was 26.7%. The ASA-resistant patients as compared with ASA-sensitive patients more often received selective cyclooxygenase 2 (COX-2) inhibitors (44% vs. 17%, respectively, p<0.05) after CABG. They had higher serum creatinine levels at the 1st day after CABG (153.7±49.9mmol/L vs 115.3±29mmol/L, respectively, p=0.028), >and very high erythrocyte sedimentation rate at 10th day after CABG (80.625±21.3 mm/h vs 54.6±26.5 mm/h; respectively, p=0.028). 33% of patients had resistance to en-teric form of ASA during 10-day therapy after CABG, however, platelet aggregation induced by arachidonic acid was low in in vitro platelet incubation with ASA. This points at decreased bioavailability of enteric forms of ASA. "Transient" ASA-resistance was detected in 12.5% of ASA-resistant patients on the 1st day after CABG due to cardiopulmonary bypass. Significant differences in the dielectric characteristics of blood and platelets were found in the groups of ASA-resistant and ASA-sensitive patients 10 days after CABG. Conclusion. Cardiopulmonary bypass, COX-2 inhibitors, renal dysfunction, the inflammatory response, may be possible reasons of the ASA-resistance after CABG. Changes in dielectric parameters of blood and platelets were found in the ASA-resistant patients.